A study on customer loyalty characteristics and satisfaction level of the customers towards Spencer’s retail outlets in Chennai - Venkatesa Palanichamy N; Vidya B; Kalpana M; Balakrishnan N; Santhosh Kumar M (The Bioscan, 2023)
Retailing which is a dynamic industry by its very nature is experiencing an explosive modernization as investment rushes into developing markets. Supermarkets are significant retailers where customers buy daily necessities. Recently, supermarkets have focused on loyalty as a measure of success, productivity, and profitability. The study investigates customer loyalty characteristics and satisfaction levels towards Spencer’s retail outlets in Chennai. Utilizing a stratified probability random sampling method, data was collected from 200 consumers across nine selected outlets and analyzed using percentage analysis, chi-square tests, and multidimensional scaling techniques. Results reveal insights into four dimensions of loyalty—cognitive, affective, conative, and action—along with aspects of trust, relationship, and commitment. Key findings indicate general customer loyalty towards Spencer’s, with high satisfaction in areas like location, customer service, and quality, but dissatisfaction in product range, cleanliness, and promotional communication. No significant association was found between age and recommendations or future purchasing intent. The study suggests that Spencer’s can further improve customer loyalty by focusing on targeted services and promotions for different age groups, enhancing product availability, and creating a pleasant store ambiance.